2005
DOI: 10.1256/qj.04.20
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of incremental 4D‐Var using non‐tangent linear models

Abstract: SUMMARYWe investigate the convergence of incremental four-dimensional variational data assimilation (4D-Var) when an approximation to the tangent linear model is used within the inner loop. Using a semi-implicit semi-Lagrangian model of the one-dimensional shallow water equations, we perform data assimilation experiments using an exact tangent linear model and using an inexact linear model (a perturbation forecast model). We find that the two assimilations converge at a similar rate and the analyses are also s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
84
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 20 publications
(12 reference statements)
0
84
0
Order By: Relevance
“…The locally iterated (extended) Kalman filter (IKF) is a Gauss-Newton method for approximating a maximumlikelihood estimate Bell and Cathey (1993), and actually it is algebraically equivalent to nonlinear three dimensional variational (3D-Var) analysis algorithms (Cohn, 1997). Later, Bell (1994) showed that the iterated Kalman smoother (IKS) represents a Gauss-Newton method to obtain an approximate maximum likelihood, as was shown later for incremental 4D-Var (Lawless et al, 2005) and has been summarised in section 3.1 above. Thus, the IKF (as the IKS) circumvents the need for choosing a step size, which is sometimes a source of difficulty in descent methods.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The locally iterated (extended) Kalman filter (IKF) is a Gauss-Newton method for approximating a maximumlikelihood estimate Bell and Cathey (1993), and actually it is algebraically equivalent to nonlinear three dimensional variational (3D-Var) analysis algorithms (Cohn, 1997). Later, Bell (1994) showed that the iterated Kalman smoother (IKS) represents a Gauss-Newton method to obtain an approximate maximum likelihood, as was shown later for incremental 4D-Var (Lawless et al, 2005) and has been summarised in section 3.1 above. Thus, the IKF (as the IKS) circumvents the need for choosing a step size, which is sometimes a source of difficulty in descent methods.…”
mentioning
confidence: 89%
“…Incremental 4D-Var has been shown to be an inexact GaussNewton method applied to the original nonlinear cost function (Lawless et al, 2005). As we assume GaussianR and P b 0 and a perfect-model framework except for the sources of model uncertainty in z 0 , the conditional mode given by the linear least 5 squares minimization (12) is the same that the conditional mean (also called the minimum variance estimate) given by the explicit solution…”
mentioning
confidence: 99%
“…The method is equivalent to solving the full nonlinear 4D-Var problem using a Gauss-Newton method (Lawless et al, 2005). The algorithm for 3D-FGAT is very similar to incremental 4D-Var, except that the tangent linear model is approximated by the identity, so that in the linearized cost function (1) we have δx i = δx 0 for all times t i .…”
Section: Assimilation Schemesmentioning
confidence: 99%
“…The system is discretized using a semiimplicit semi-Lagrangian integration scheme, as described in Lawless et al (2003). We define the problem on a periodic domain of 1000 grid points, with a spacing x = 0.01 m between them, so that x ∈ [0 m, 10 m] and assume a model time step t = 0.0092 s. Other parameters for the problem are as defined in Lawless et al (2005). A 3D-FGAT scheme for this system is set up over a time window [−T, T], with observations of u and φ at every spatial point at times −T, 0, T. The true state at time −T is defined using the initial conditions from Case I of Lawless et al (2005) and we take T = 0.23, so that there are 50 time steps in the assimilation interval.…”
Section: Shallow-water Modelmentioning
confidence: 99%
See 1 more Smart Citation